Whistler-mode instability in magnetospheres of Uranus and Neptune - Tripathi A.K.; Singhal R.P. (My University, 2025)
Whistler-mode instability in the magnetospheres of the outer planets Uranus and Neptune is investigated using an anisotropic kappa loss-cone distribution and comparisons have been made with the observations made by Voyager 2. Normalized temporal growth rates have been evaluated numerically at two representative radial distances at each planet. Parametric studies have been performed by changing plasma parameters: cold and hot electron densities, hot electron temperature and temperature anisotropy. It is found that whistler-mode emissions observed at lower radial distances cannot be reproduced in our calculations. Electron pitch-angle diffusion and energy diffusion coefficients have been obtained using the calculated growth rates. The present calculations show that electrons of energy above about 20 keV may be able to precipitate into the planetary atmospheres of both planets. Present studies should be helpful in making estimates on scattering properties of whistler-mode waves and thus contribute to a better understanding of the auroral activity in the planetary atmospheres. © 2007 Elsevier Ltd. All rights reserved.